Agreement between a swept-source optical coherence tomography and dual Scheimpflug Placido analyser in healthy, keratoconus suspect and keratoconus eyes - Mohd. Asyraaf, Abdul Kadir; Muhammad Adri, Mohamed Shafit; Adzura, Salam; Khairidzan, Mohd Kamal (Springer Nature, 2026)
Purpose To evaluate the agreement and interchangeability of anterior and posterior corneal parameters measured by the swept-source optical coherence tomography–based ANTERION and the dual Scheimpflug–Placido GALILEI G4 in normal, keratoconus suspect (KS), and keratoconus (KC) eyes. Methods In this cross-sectional study, 221 eyes (129 normal, 40 KS, 52 KC) were examined using ANTERION and GALILEI G4 in a single session. Anterior and posterior keratometry (K1, K2, K Max), best-fit sphere (BFS), central corneal thickness (CCT), and minimum corneal thickness (MCT) were analysed. Inter-device agreement was assessed using paired statistical tests and Bland–Altman analysis. Results In normal eyes, most parameters showed statistically significant mean differences with wide limits of agreement (LoA). In KS eyes, no significant differences were observed in each parameter. In KC eyes, mean differences were minimal, though LoAs were wide, particularly for anterior keratometry and pachymetry; only MCT showed a statistically significant difference. Pachymetric measurements consistently differed between devices, with ANTERION generally reporting smaller values. Conclusion The wide LoAs between ANTERION and GALILEI indicate that the devices are not interchangeable, particularly for longitudinal monitoring in keratoconus. Consistent use of a single device is recommended in clinical practice.